EVALUATION OF COMPLIANCE WITH THE IMPLEMENTATION OF HEALTH PROTOCOLS IN PUBLIC PLACES DURING THE COVID-19 PANDEMIC IN GORONTALO DISTRICT - Yasir Mokodompis; Zul Fikar Ahmad (Universitas Negeri Gorontalo, 2021)
The COVID-19 pandemic has an impact in all lives and is continuing. Some of the efforts to prevent transmission are to continue monitor health protocols. This study aims to obtain an overview of the application of health protocols in public places during the Covid 19 pandemic in Gorontalo District. This research was conducted in three sub-districts in Gorontalo district with different areas. This research uses a quantitative design, with a descriptive survey research type. The population in this study are public places that include government offices, private offices, places of worship, markets / centers, and terminals. The results of the analysis showed that the health protocol protocol in public places was 38.5%. There is no significant differences were found between inside and outside the building. Health protocol sign has no relationship with community compliance in public places. To prevent further transmission, we provide several policies: Maximizing the role of resilient villages COVID-19. Increasing supervision of public places, Evidence-Based Policy, re-involving health cadres and village officials in conducting tracing contacts.